Urethral advancement technique for repair of distal penile hypospadias: A revisit - Mohamed, M.S Awad (Indian Journal of Plastic Surgery, 2006)
Background: Numerous ingenious methods have been described to repair hypospadias with variable results. The anterior urethral advancement technique reported by Chang[1] to repair distal hypospadias has shown encouraging results. We have reevaluated this technique with some modifications to improve its results.Materials and Methods: This study was done on 72 patients, 19 cases with glanular hypospadias, 20 cases with coronal hypospadias, 22 cases of subcoronal hypospadias,and 11 cases with anterior penile hypospadias in the period between September 1999 and October 2003. The patients′ age ranged from two years to twenty five years (median age 5.6) years. All the patients were operated using Chang′s technique with our modifications. Results: There were no major complications in any of our patients, no postoperative fistulae or urethral stricture. Three patients had meatal stenosis and preputial edema occurred in 83.3% in non-circumcised patients.Conclusion: Modifications of the anterior advancement technique has produced excellent Results. It is easy to do and learn and also offers good cosmetic and functional results.
Keywords: Advancement; hypospadias; urethra